Combining carbonic anhydrase and thioredoxin reductase inhibitory motifs within a single molecule dramatically increases its cytotoxicity - Mikhail Krasavin; Tatiana Sharonova; Vladimir Sharoyko; Daniil Zhukovsky; Stanislav Kalinin; Raivis Žalubovskis; Tatiana Tennikova; Claudiu T. Supuran (Taylor & Francis Group, 2020)
A hypothesis that simultaneous targeting cancer-related carbonic anhydrase hCA IX and hCA XII isoforms (whose overexpression is a cancer cell's defence mechanism against hypoxia) along with thioredoxin reductase (overexpressed in cancers as a defence against oxidative stress) may lead to synergistic antiproliferative effects was confirmed by testing combinations of the two inhibitor classes against pancreatic cancer cells (PANC-1). Combining both pharmacophoric motifs within one molecule led to a sharp increase of cytotoxicity. This preliminary observation sets the ground for a fundamentally new approach to anticancer agent design.